Effect of long-term application of epinephrine on rat skin vasculature: Experimental study - (:unkn) unknown (My University, 2002)
As a potent vasoconstrictor, epinephrine is used ubiquitously in plastic surgery. It is typically delivered subcutaneously in very low concentrations over a brief time interval. We are aware of no reports describing the long-term release of epinephrine as an independent agent to the soft tissues for the purpose of causing prolonged local vasoconstriction. This study was designed to address two goals: first, to investigate the effect of long-term local release of epinephrine from a drug delivery system on rat abdominal skin vasculature; secondly, to evaluate the pharmacological properties of this drug delivery system (DDS). Thirty male Sprague-Dawley rats, weighing 300-400 g, were included in the study. Animals were subdivided into two groups of 15 each. Group A (control group) and Group B (experimental group) were treated with saline and epinephrine-loaded microspheres (msps), respectively. The manufacturing process and formulation studies of the DDS are described. In vivo assays revealed a 7-day sustained release of epinephrine. After 7 days, neither residual nor supraphysiologic release of epinephrine was shown with high-performance liquid chromatography (HPLC). Histological studies with hematoxylineosin and periodic acid Schiff revealed a statistically significant increase in number of vessels as well as their diameter and wall thickness (P <0.05). Epinephrine release via this msp/DDS predictably induces local vasoconstriction over a time sequence known to be optimally associated with hypoxia and promotion of vascular augmentation. This model can be valuable in sustaining hemostasis during long-lasting (more than a few hours) surgical procedures by its long-acting vasoconstructive effect. The system's ability to intentionally cause vascular augmentation also bodes great potential in flap and graft surgery. © 2002 Wiley-Liss, Inc.